Mondor disease of the penis in a young patient - Erich Roberto Ramón Núñez; Carina Flora Salgado Reyes; Hilda Marlene Ramón Núñez (Centro Provincial de Información de Ciencias Médicas, 2021)
The case report of a 21 years patient with history of right inguinal herniorrhaphy is presented, who attended control visit and he made reference to an induration and pain in the dorsal region of the penis with 4 days of evolution that had begun after a sexual relationship in which he consumed marihuana. In the physical exam the penis dorsal vein was found thicken, hard and painful to the palpation. He was diagnosed a Mondor disease of the penis. The Doppler scanning confirmed the thrombophlebitis of this vein. The patient received medical treatment and had a favorable clinical course.